Lasmiditan for acute migraine treatment. (November 2013) - Neeb, Lars; Reuter, Uwe
Lasmiditan is a new neurally acting antimigraine drug that acts as a highly selective serotonin1F receptor agonist. Its chemical structure is distinctly different from that of triptans. Its dose-dependent clinical efficacy was proven in two clinical Phase II trials using intravenous and oral formulations. Oral lasmiditan showed significant headache relief after 2 h at doses of 50, 100, 200 and 400 mg. Adverse events of lasmiditan were dose-dependent and mainly associated with the CNS. They predominantly included dizziness, paresthesia and fatigue, and were mostly mild-to-moderate in intensity. Preclinical studies showed that, unlike triptans, lasmiditan lacks any vasoconstrictive activity, which makes it a promising drug for patients with contraindications to triptans owing to cardio- or cerebro-vascular diseases, or an elevated vascular risk profile.